Assessing the speed of improved postharvest technology adoption in Tanzania: the role of social learning and agricultural extension services - Manda, J.; Feleke, S.; Mutungi, C.; Tufa, A.H.; Mateete, B.; Abdoulaye, T.; Alene, A.D. (Elsevier, 2024)
The Purdue Improved Crop Storage (PICS) bag is often associated with preventing grain damage from insect infestation, reducing aflatoxin accumulation in stored grain, and avoiding exposure to hazardous storage chemicals. However, limited knowledge is available on the information channels driving the adoption of the technology. Using data from 429 households, this study examines the impacts of social learning and extension services on the speed of adoption of PICS bags in Tanzania. We utilized the doubly robust multivalued inverse probability weighted regression (MIPWRA) model to estimate the impact and the Laplace regression model to evaluate the heterogeneous effects of the two information channels. The impact results indicate that social learning and extension services reduce the time to adopt PICS bags by 51 % and 49 %, respectively. Moreover, the speed at which farmers adopted the technology was faster when using the two information channels jointly (61 %) than individually. The Laplace regression model results show that the marginal impacts of the two channels are higher for the households in the upper quantiles of the distribution, compared to the lower quantiles representing the early adopters. Designing policies that account for different adopter groups (innovators, early adopters, early majority, late majority, and laggards) is therefore essential.